Comparison of Serum Beta Human Chorionic Gonadotropin (S. b-HCG) Level in Preeclamptic and Normal Pregnancy - Khanam, Suraiya; Rouf, Salma; Sultana, Chowdhury Shamima; Ferdous, Mst Sharmin; Saha, Kabita (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Preeclampsia is a major cause of feto maternal morbidity and mortality worldwide. WHO estimated the incidence to be seven times higher in developing countries than in developed countries (2.8% of live births versus 0.4%). Overall preeclampsia/ eclampsia accounts for 10%–15% of maternal deaths. Exact etiology of the disease is unknown. Objective: To compare the serum b-HCG levels in preeclamptic and normal pregnant women. Methods: This case-control study was carried out in the Department of Obstetrics & Gynecology, Dhaka Medical College and Hospital, Dhaka, during July 2017 to June 2019 to evaluate the serum b-HCG level in preeclamptic and normal pregnant women. This study compare the b-HCG levels between the two groups as well as find out the association of serum b-HCG level with severity of preeclampsia. A total 80 women with ³37 weeks of gestation admitted into the Department, who fulfilled the inclusion criteria were enrolled. Out of 80 pregnant women 40 with preeclampsia and rest 40 normal pregnant women were considered as case (Group I) and control (Group II) respectively. Serum b-HCG level of all the women were determined in the Departments of Biochemistry and Molecular Biology, Bangabandhu sheikh Mujib Medical University. Statistical analysis of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-22.0). Result: The mean systolic blood pressure was 175.3±10.1 mmHg in group I and 113.1±14.0 mmHg in group II. The mean diastolic blood pressure was 106.75±10.47 mmHg in group I and 72.3±8.0 mmHg in group II. The difference was statistically significant (p<0.05). The mean b-HCG was 42235±34491 IU/L in group I and 29224±21022 IU/L in group II. The difference was statistically significant (p<0.05). The mean b-HCG was 27664.9±18076.4 IU/ L in mild preeclampsia and 48474.7±31554.1 IU/L in severe preeclampsia. The difference was also found statistically significant (p<0.05) between two groups. No difference in Serum b-hCG was found between mild preeclampsia and normal pregnancy. Conclusion: Significantly high level of Serum b-hCG was found in the preeclamptic compared to the normal pregnant women. Serum b-hCG level also found raised according to the severity of preeclampsia due to hyperplasic trophoblastic cells of placenta. The maternal serumb- hCG plays one of the important role in the pathogenesis of preeclampsia and its severity. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(1): 25-31